THE DECISION MAKING PROCESS AND WEAK SIGNAL TREATMENT - Fonseca, Fernando (2012)
Along day to day conduction of organizational activities, several decisions are taken, some of which are merely operational whilst others directly influence corporate strategy. To treat issues pertaining to organizational strategy, many companies devote effort concerning the monitoring of the competitive environment which, despite bringing forth positive results to the corporation, is not naturally reflected in routine activities. One of the most proactive ways to monitor the competitive environment is treating weak signals which, given their distinctive characteristics, are able to demonstrate, in an anticipated manner, the occurrence of strategically relevant events. This article develops a theoretical analysis concerning these practices, starting off with conceptualizations, their similarities and seminal aspects of activities and characteristics of both fields: the occurrence of individual and organizational biases, the use of processual models and methodologies, the need for interpretation, organizational learning and the use of intuition. A theoretical approach concerning these two apparently distinct practices demonstrates that many of their characteristics are similar. This allows for the suggestion that, once the organization presents any initiative in whatever type of processual organization decision making, or given the consolidation of a treatment process for weak signals, resources might be reduced and results multiplied.